Trzy kody w przekładzie «Σήμα κινδύνου» Antoniego Samarakisa na polski – studium przypadku - Ciesielczyk, Natalia (Investigationes Linguisticae, 2010)
Translating from and into less widely known languages has always been problematic as there has always been a lack of people proficient in them. This may be the reason why so few examples of the extremely rich and diverse Modern Greek literature were translated into Polish. In addition, most of them were translated from a third language (langue pivot), that is in most cases from English and French. This might have caused some difficulties, as the translators who intended to translate Greek literature did not know the Greek culture and heritage. One of such examples is the book «Σήμα κινδύνου», written by Antonis Samarakis, which was translated into Polish from its English version titled “Danger Signal” by Halina Cieplińska. In this paper I would like to analyze the Polish translation of this book from the point of view of Maria Krysztofiak’s theory about three codes (lexical-semantic, cultural and aesthetic code) which have to be harmoniously joined in order to create a good literary translation.